Pooling money the future of mutual funds - Fuchita, Yasuyuki, 1958-; Litan, Robert E., 1950- (Nomura Institute of Capital Markets Research ; Brookings Institution Press, 2008)
"Experts from the United States and Japan look at forces of change in their securities markets and offer their views of the future for mutual funds and other forms of securities diversification"--Provided by publisher.